2002
DOI: 10.1177/154405910208100504
|View full text |Cite
|
Sign up to set email alerts
|

Severe Impairment of Secretory Ig Production in Parotid Saliva of Down Syndrome Individuals

Abstract: Infections associated with Down Syndrome (DS) are prevalent in the mucosal-gastrointestinal and respiratory systems, for reasons that are uncertain. The purpose of the present study was to assess the levels of parotid salivary immunoglobulins (Ig) in a group of DS individuals as a possible factor in the susceptibility of mucosal surfaces to infections. Twenty-nine DS and 10 age- and sex-matched healthy individuals were included. Salivary flow rate and IgA, IgG, and IgM concentrations were recorded. The secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 32 publications
0
28
0
4
Order By: Relevance
“…26 The immunodeficiency in Down syndrome children has caused the decreasing number of T cells, and if in immaturity condition, it can make the incidence of periodontal disease in those children increased, but not the incidence of dental caries. 1,5,14 It is because the components of immune system in oral cavity in periodontal disorders include neutrophils, antibodies, lymphocytes, macrophages, lymphokine, secretory immune system. However, the level of sIgA in periodontal disorders is not increased since unlike dental caries process, in periodontal disease sIgA is considered as the most responsible immune component.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 The immunodeficiency in Down syndrome children has caused the decreasing number of T cells, and if in immaturity condition, it can make the incidence of periodontal disease in those children increased, but not the incidence of dental caries. 1,5,14 It is because the components of immune system in oral cavity in periodontal disorders include neutrophils, antibodies, lymphocytes, macrophages, lymphokine, secretory immune system. However, the level of sIgA in periodontal disorders is not increased since unlike dental caries process, in periodontal disease sIgA is considered as the most responsible immune component.…”
Section: Discussionmentioning
confidence: 99%
“…1,14 Some researches even have found that high rate of infection in Down syndrome patients is caused by immune system disorders. 1,14 This can be shown by a defect in neutrophil chemotaxis of PMN leukocytes, antibody response damage against specific pathogens, decreasing number of T lymphocyte cells and immaturity of lymphocyte cells T.…”
Section: Characteristics Of Systemic Down Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…However, there are marked methodological differences between most of these sialochemical studies. These differences could be attributed to a wide diversity of procedures for quantitation, fractionation and detection of proteins (6,7,11,12,13,27), the lack of standard for saliva collection (1), analysis of different subtypes of saliva, low number of saliva donors specially when glandular salivas are studied (5,29) and analytical assessments of pools of salivas provided by different subjects (25). As a whole, these variations have resulted so far in a lack of recognizable basic protein profiles of human saliva that could be associated with normality.…”
mentioning
confidence: 99%